2009
DOI: 10.1210/me.2008-0432
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Induces Abdominal Obesity Via GHS-R-Dependent Lipid Retention

Abstract: Circulating ghrelin elevates abdominal adiposity by a mechanism independent of its central orexigenic activity. In this study we tested the hypothesis that peripheral ghrelin induces a depot-specific increase in white adipose tissue (WAT) mass in vivo by GH secretagogue receptor (GHS-R(1a))-mediated lipolysis. Chronic iv infusion of acylated ghrelin increased retroperitoneal and inguinal WAT volume in rats without elevating superficial sc fat, food intake, or circulating lipids and glucose. Increased retroperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 45 publications
4
78
2
Order By: Relevance
“…In another report, a low dose of ghrelin administered peripherally produced an increase in FAS and decreases in CPT‐1α mRNAs expression without affecting food intake. Although some reports have shown an increase in liver adiposity with ghrelin treatment (Davies et al ., 2009), others have shown the opposite effect with ghrelin preventing fat accumulation and improving redox state in the liver of high fat‐fed animals (Barazzoni et al ., 2013) but also under caloric restriction (Stark et al ., 2015). Additional factors may account for the differences in results reported by different groups: mouse age and strain, subchronic vs. chronic ghrelin treatment and via of administration (central vs. peripheral).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another report, a low dose of ghrelin administered peripherally produced an increase in FAS and decreases in CPT‐1α mRNAs expression without affecting food intake. Although some reports have shown an increase in liver adiposity with ghrelin treatment (Davies et al ., 2009), others have shown the opposite effect with ghrelin preventing fat accumulation and improving redox state in the liver of high fat‐fed animals (Barazzoni et al ., 2013) but also under caloric restriction (Stark et al ., 2015). Additional factors may account for the differences in results reported by different groups: mouse age and strain, subchronic vs. chronic ghrelin treatment and via of administration (central vs. peripheral).…”
Section: Discussionmentioning
confidence: 99%
“…However, its role on hepatic steatosis is not known. Recent publications have suggested that it may increase liver adiposity through p53 signaling (Davies et al ., 2009; Porteiro et al ., 2013), although others have shown the opposite effect with ghrelin preventing fat accumulation and improving redox state in the liver of high fat‐fed animals (Barazzoni et al ., 2013) and also under pair‐feed conditions (Stark et al ., 2015). The goal of this work was to determine whether deletion of ghrelin might prevent the age‐associated NAFLD and to determine whether its effects are mediated through the p300‐C/EBPα/β pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Thompson et al (3) observed parallel adipogenic effects of UAG with AG, via a mechanism independent of the GHS-R 1a in rats. Davies et al (24) observed that a chronic infusion of AG induced abdominal obesity, whereas UAG had no effect on adiposity in rats.…”
Section: Discussionmentioning
confidence: 99%
“…X/A-like cells of the oxyntic glands in the stomach produce the majority of ghrelin, and smaller amounts are secreted by other organs, such as the intestine, pancreas, kidney, and hypothalamus [15,16]. Ghrelin has several physiological functions in addition to the secretion of GH, including the promotion of the appetite signal that antagonizes leptin in the hypothalamus [17], stimulation of gastrointestinal activity (e.g., peristalsis, gastric acid secretion, and pancreatic excretion through the vagal nerves) [18], and regulation of fat metabolism [19] (Table 1). Ghrelin also mitigates proinflammatory cytokine production and attenuates the stress signal [20].…”
Section: The Discovery Of Ghrelin and Its Featuresmentioning
confidence: 99%